Academics and teachers' perceptions of remote teaching during the Covid-19 pandemic (Research, Society and Development, 2022)
Due to the Covid-19 pandemic, face-to-face teaching started to be developed remotely, with the aid of digital technologies, while educational institutions needed to quickly adapt to the new format to maintain the planned activities. The aim of this study is to verify the perception of students and professors of the Accounting Course in relation to remote teaching developed during the pandemic period. The research in question is qualitative and it is a case study, the instrument used for data collection was interviews. The main results to be highlighted were: the necessary adaptation to the new teaching format, as well as reconciling studies and home office, the increase in the number of tasks that imposed personal organization and group work. Linked to these factors and the distance, dialogue became a strong and necessary point for conducting activities between professors and undergraduates.